Pengaruh Pemberian Pupuk Hayati Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays L.) - Leli Annisah Hasibuan; Parmanoan; Meiliana Friska (Journal Agro-Livestock, 2024)
Sweet corn (Zea mays L., saccharata) is one of the commodities that is widely cultivated by farmers in Padangsidimpuan City. Efforts to increase sweet corn production continue to be made, one of the efforts that can be made to increase corn production is by providing fertilizer. Biofertilizer technology is the use of active biological products consisting of soil-fertilizing microbes to increase fertilization efficiency, fertility and soil health. Biofertilizers can reduce the use of chemical fertilizers by up to 75%. The aim of this research is to determine the effect of providing biological fertilizer on the growth and production of sweet corn (Zea mays L.). The research method used a Randomized Block Design (RAK), with one (1) treatment factor and three (3) replications. The treatments in this study were as follows: P0 = Control, P1 = 1% biological fertilizer, P2 = 2% biological fertilizer, P3 = 3% biological fertilizer, P3 = 4% biological fertilizer, P5 = 5% biological fertilizer. The results of this research were the application of real biological fertilizer to plant height of 8 WAP, leaf width of 8 WAP, leaf length of 8 WAP, weight of cob cobs. Treatment with 3% biofertilizer (P3) produces cob length equivalent to applying 0% biofertilizer (P0)